Position feedback dynamic surface control for pneumatic actuator position servo system. Issue 1 (1st January 2018) - Lin, Weiyang; Guan, Renhe; Yuan, Letian; Li, Zhan; Tong, Mingsi
ABSTRACT: Pneumatic servo system is widely utilized in many industries, which has huge potential to replace hydraulic and electromechanical system due to its low-cost, high power quality ratio and quick response. There have been considerable control methods proposed to complete pneumatic position servo control. However, these methods still have some inevitable problems which remain to be settled. In this paper, a position feedback dynamic surface control is applied to the pneumatic system based on our pneumatic actuator model in order to provide a new idea for pneumatic position control. Considering model uncertainties, external force disturbance and noise interference, a modified dynamic surface controller is developed to overcome their negative effects. Besides, the stability of the pneumatic system with the modified controller is proved by Lyapunov's stability theorem. Moreover, the results of simulation and pneumatic experiment also verify that the dynamic surface controller is more advantageous than the traditional PID controller in pneumatic position servo control.